Recurrent disease after treatment for cervical intraepithelial neoplasia—The importance of a flawless definition of residual disease and length of follow-up. (May 2020) - Bjørnerem, Mathilde Seeger; Sørbye, Sveinung Wergeland; Skjeldestad, Finn Egil
Abstract: Objective: To evaluate adherence to national guidelines for follow-up, and assess residual and recurrent disease after treatment for cervical intraepithelial neoplasia grade 2 or worse (CIN2+). Study design: In a case-series design women aged 25–69 years treated for primary CIN2+ in 2006–2011 (n = 752) were followed through August 9, 2019 for residual or recurrent disease, i.e., CIN2+ diagnosed before or after, respectively, two consecutive, normal post-treatment cytology results. We used the Chi-Square test to assess predictive factors of adherence to post-treatment follow-up and residual disease, and survival analyses to assess the cumulative incidence of residual and recurrent disease. Results: Strict adherence to post-treatment follow-up was low . However, 702 (95 %) women attended at least one post-treatment follow-up visit within the suggested time window. Forty-two women (5.6%) were diagnosed with residual disease, 38 (91 %) of whom were diagnosed within 2 years of treatment. Among the 637 (85 %) women with two consecutive, normal post-treatment cytology results, cumulative incidence of recurrent disease was 1.0 (95 % confidence interval [CI]: 0.2–1.8) and 2.5 (95 % CI: 1.2–3.8) per 100 women-years within 42 and 78 months of treatment, respectively. Three women with residual and two with recurrent disease were diagnosed with cervical cancer within 78 months of treatment. Women with not-free resection margins at treatment had a significantly increased risk of residual and recurrent disease. Using a 2-year definition for residual disease would misclassify 3 of 5 cancer cases as recurrent disease when they were true cases of residual disease. Conclusions: This study emphasizes the importance of properly distinguishing between residual and recurrent disease after treatment for CIN2 + . Many women with residual disease could benefit from an earlier colposcopy, cervical biopsy, or diagnostic conization during post-treatment follow-up in order to detect occult cervical cancer. The cumulative incidence of recurrent disease within 78 months of treatment was low.